AB1323-HPR A QUALITATIVE EXPLORATION OF THE PERSONAL FINANCIAL TOLL OF ARTHRITIS. (2nd June 2020) - Berkovic, D.; Ayton, D.; Briggs, A. M.; Ackerman, I.
Abstract : Background: The financial experience faced by working-age people with arthritis includes living below the poverty line for many (1). Financial distress amongst people with arthritis is known to contribute to poorer health outcomes, including high psychological distress and more severe pain (2). Despite the demonstrated societal cost of arthritis care and management, the personal costs borne by the individual are not well understood in different health systems (3). Objectives: To explore the perceived financial impacts of living with arthritis amongst working-age individuals aged 18 – 50 years in Australia. Methods: A qualitative descriptive study design was used. Participants with inflammatory arthritis or osteoarthritis were recruited from the community, including urban and rural settings. An interview schedule was developed, informed by existing literature (4), which was piloted prior to data collection. Deductive and inductive coding techniques were used to identify financial-related themes arising from the data. Results: Semi-structured interviews were conducted with 21 younger people (90% female) with a mix of arthritis conditions including rheumatoid arthritis, psoriatic arthritis, osteoarthritis, and ankylosing spondylitis. Four themes were identified: direct arthritis-attributable medical costs, indirect arthritis-attributable costs, insurance and pension costs, and broader financial impacts on the family. Non-subsidised costs were frequently referenced by participants as burdensome, and existed even within the publically-funded healthcare system. Financial distress was characterised by participants as chronic, onerous for the entire family, and associated with exacerbation of physical symptoms. Conclusion: People with arthritis and of working age experience significant arthritis-attributable financial burden and related distress. Financial concerns should be actively identified and considered within shared clinical decision making, in order to provide more patient-centred care for these individuals. References: [1]Rios R, Zautra AJ. (2011). Socioeconomic Disparities in Pain: The Role of Economic Hardship and Daily Financial Worry. Health Psychol. 30(1) 58-66. [2]Yilmaz V, Umay E, Gundogdu I, Kaaahmet ZO, Ozturk AE. (2017). Rheumatoid Arthritis: Are psychological factors effective in disease flare? Eur J Rheumatol. 4(2) 127-132. [3]Schofield D, Rupendra S, Cunich C. Counting the Cost Part 2: Economic Costs: The current and future burden of arthritis. The University of Sydney: Arthritis Australia; 2016. [4]Ackerman IN, Kemp JL, Crossley KM, Culvenor AG, Hinman RS. (2017). Hip and Knee Osteoarthritis Affects Younger People, Too. J Orthop Sports Phys Ther. 47(2) 67-79. Disclosure of Interests: None declared